2016
DOI: 10.1208/s12249-015-0476-9
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-laboratory in Vitro Study to Compare Data from Abbreviated and Pharmacopeial Impactor Measurements for Orally Inhaled Products: a Report of the European Aerosol Group (EPAG)

Abstract: Abstract. Fine particle dose (FPD) is a critical quality attribute for orally inhaled products (OIPs). The abbreviated impactor measurement (AIM) concept simplifies its measurement, provided there is a validated understanding of the relationship with the full resolution pharmacopoeial impactor (PIM) data for a given product. This multi-center study compared fine particle dose determined using AIM and PIM for five dry powder inhaler (DPIs) and two pressurized metered-dose inhaler (pMDI) products, one of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Similar findings referring to the higher FPF values obtained by TSI in comparison to NGI, due to the difference in the cut-off value for FPF, were observed by Omer et al [33]. Higher FPF values obtained by FSI in comparison to NGI have already been recognized as a limitation of FSI [27,70], although some studies showed no significant differences between FSI and NGI results, e.g., [23,30]. The highest level of correlation (R 2 = 0.9440) with the lowest values of RMSE and NMRSE (4.669 and 0.173, respectively) was observed between FPF results from NGI and TSI, while the correlation between NGI and FSI, and TSI and FSI results was less pronounced (Table 6).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar findings referring to the higher FPF values obtained by TSI in comparison to NGI, due to the difference in the cut-off value for FPF, were observed by Omer et al [33]. Higher FPF values obtained by FSI in comparison to NGI have already been recognized as a limitation of FSI [27,70], although some studies showed no significant differences between FSI and NGI results, e.g., [23,30]. The highest level of correlation (R 2 = 0.9440) with the lowest values of RMSE and NMRSE (4.669 and 0.173, respectively) was observed between FPF results from NGI and TSI, while the correlation between NGI and FSI, and TSI and FSI results was less pronounced (Table 6).…”
Section: Resultssupporting
confidence: 71%
“…Therefore, the availability of different in vitro methods can impede regulatory evaluation. Some studies compared two or three in vitro methods for aerodynamic assessment of DPIs [23,[26][27][28][29][30][31][32][33], but their results were inconclusive. While some of the studies indicated similarities between ACI and NGI results [26,29,31], there were also reports on diverging results obtained by these two methods [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…the medium-to-small airways and peripheral bronchioles). The FPD of an aerosol cloud is the proportion of drug mass included in aerosolized particles with an aerodynamic diameter B5.0 lm [5,30]. More than 60% of the drug dose expelled by Respimat Ò falls within an FPD of B5.0 lm [31], which accentuates sedimentation of particles in the smaller bronchi and bronchioles [32].…”
Section: Optimizing Drug Delivery To the Lungsmentioning
confidence: 99%
“…For Pulmicort® (Tubuhaler®), a decrease in MMDA was observed when increasing flow rate from 30 to 90 L/min for NGI, whose results were smaller than those obtained for ACI at 28.3, 45, and 60 L/min (YOSHIDA et al, 2017). It is important to clarify that when standardized and validated, a fair correlation between different apparatus, as abbreviated impactors and pharmacopeial impactors (NGI or ACI) can be established, as shown in a multi-laboratory study for 5 different orally inhaled products (NICHOLS et al, 2016), but there is still room for in vitro-in vivo correlation improvement. In 2009 the first organoid derived from a single stem cell was obtained, and presented capacity for self-proliferation and differentiation (XIA et al, 2019).…”
Section: Aerosolization Performance and In Vivo Correlationmentioning
confidence: 93%